Conflicting Interpretations of Holiness and Heterodoxy in Late Medieval Italy - Janine Larmon Peterson (I Quaderni del MAES, 2024)
In thirteenth- and fourteenth-century Italy, there are a number of examples of people that local communities perceived as holy, but who ran afoul of inquisitors.  Two of the more lesser-known, but extremely polarizing local saints ― and accused heretics― were Meco del Sacco and Tomassuccio of Nocera.  In both cases, the impetus for the accusations seemed to be jealousy from other members of the clerical elite.  In addition, local politics played an enormous part in the championing, or defaming, of their sanctity.  In both cases, the accused successfully challenged the charges of heresy.  The histories of Meco del Sacco and Tomassuccio of Nocera demonstrate how accused individuals could contest inquisitorial authority, and exemplify how the thin line between sanctity and heresy could give rise to separate realities, creating a liminal space within which a single individual could co-exist.